Adherence to nutritional guidelines in pregnancy: evidence from the Growing Up in New Zealand birth cohort study - Susan Morton; Cameron Grant; Clare Wall; Polly E Atatoan Carr; Dinusha Bandara; Johanna Schmidt; Vivienne Ivory; Hazel Inskip; Carlos A. Camargo (2014)
To determine adherence to nutritional guidelines by pregnant women in New Zealand and maternal characteristics associated with adherence.